The light-responsive oxidase-like activity of MIL-125-NH2@Pd and its application in the determination of casein phosphopeptides. Issue 14 (20th March 2023) - Yin, Shi-Jun; Li, Li-Xian; Yang, Feng-Qing
Abstract : MIL-125-NH2 with uniform palladium distribution is synthesized through a simple solvothermal method. Based on the excellent light-responsive oxidase-like activity of MIL-125-NH2 @Pd, a sensing strategy is developed for the selective detection of CPP. Abstract : A polyhedral MIL-125-NH2 @Pd nanoparticle with light-responsive oxidase-like activity was synthesized through a simple solvothermal method and was characterized by field emission scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray powder diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis, Brunauer–Emmett–Teller analysis, etc. MIL-125-NH2 @Pd can catalyze the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) under light radiation without H2 O2, indicating its intrinsic light-responsive oxidase-like characteristic. MIL-125-NH2 @Pd shows a superior catalytic activity and higher affinity to TMB, compared to MIL-125-NH2, owing to the presence of homogenously distributed palladium (Pd) nanoparticles. The results of the mechanism study indicate the existence of ˙O2 − and electron holes during the catalytic reaction of MIL-125-NH2 @Pd. Furthermore, based on the excellent light-responsive oxidase-like activity and specific recognition capacity for casein phosphopeptides (CPP) of titanium ions (Ti 4+ ) in MIL-125-NH2 @Pd, a simple colorimetric sensing platform was developed for the determination of CPP in a linear range of 10–100 μg mL −1 with a limit of detection as low as 2.9 μg mL −1 . Finally, the developed method was successfully employed in the sensitive and selective detection of CPP in spiked rabbit and rat plasma samples. This study may provide a reliable and highly efficient strategy to realize the excitation-responsive sensing applications of materials.